Policy Connectivity and Fiscal Decentralization in Encouraging Economic Development through Marine Tourism in Banten Province - Nugroho, Arif; Jumanah, Jumanah; Stiawati, Titi; Handoko, Pryo (International Publisher (YAPENBI), 2026)
This study analyzes the role of fiscal and administrative decentralization and policy connectivity in the development of marine tourism as a driver of economic development in Banten Province. Using a mixed-methods approach, the study combines quantitative analysis of GRDP data, tourism sector contributions, the number of destinations, and investment indicators with qualitative analysis through in-depth interviews, focus group discussions, and field observations. The results show that while decentralization provides flexibility for local governments in destination management and budget allocation, its effectiveness depends heavily on vertical and horizontal policy integration and cross-sectoral coordination. Disparities in tourism contributions between districts remain high, but good policy connectivity can increase GRDP per capita by between five and seven percent, create new jobs, encourage investment, and empower local MSMEs. These findings confirm that effective marine tourism management requires synergy between multi-level governance, active community participation, and data-driven decision-making to achieve inclusive, sustainable, and resilient economic development.